Analisis Pengaruh Tata Kelola Perusahaan, Kinerja Lingkungan, dan Kinerja Sosial terhadap Kinerja Keuangan pada Perusahaan Manufaktur Sektor Barang Konsumsi di BEI (2017–2021) - Agustina, Reza (Journal of Economic, Management and Entrepreneurship, 2024)
This study aims to provide empirical evidence regarding the influence  of Corporate Governance disclosure, Environmental Performance, and Social Performance on financial performance in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) during the period 2017–2021. The data used is secondary data obtained from the company's financial statements. The dependent variables in this study are financial performance measured using Return on Assets (ROA), while the independent variables include Corporate Governance, environmental performance, and social performance. The research sample consisted of 18 companies selected through the purposive sampling method. The analysis method used is simple linear regression, with data analysis techniques that include descriptive analysis as well as classical assumption testing